Investigating the viability of a framework for small scale, easily deployable and extensible hotspot management systems - Thinyane, Mamello P (Rhodes University, Faculty of Science, Department of Computer Science, 2006)
The proliferation of PALs (Public Access Locations) is fuelling the development of new standards, protocols, services, and applications for WLANs (Wireless Local Area Networks). PALs are set up at public locations to meet continually changing, multiservice, multi-protocol user requirements. This research investigates the essential infrastructural requirements that will enable further proliferation of PALs, and consequently facilitate ubiquitous computing. Based on these requirements, an extensible architectural framework for PAL management systems that inherently facilitates the provisioning of multiple services and multiple protocols on PALs is derived. The ensuing framework, which is called Xobogel, is based on the microkernel architectural pattern, and the IPDR (Internet Protocol Data Record) specification. Xobogel takes into consideration and supports the implementation of diverse business models for PALs, in respect of distinct environmental factors. It also facilitates next-generation network service usage accounting through a simple, flexible, and extensible XML based usage record. The framework is subsequently validated for service element extensibility and simplicity through the design, implementation, and experimental deployment of SEHS (Small Extensible Hotspot System), a system based on the framework. The robustness and scalability of the framework is observed to be sufficient for SMME deployment, withstanding the stress testing experiments performed on SEHS. The range of service element and charging modules implemented confirm an acceptable level of flexibility and extensibility within the framework.
Keywords: Local area networks (Computer networks); Computer networks -- Management; Computer network architectures; Computer network protocols; Wireless communication systems; XML (Document markup language)